HUBUNGAN KUALITAS PRODUK, HARGA, DISTRIBUSI DAN STRATEGI PROMOSI TERHADAP KEPUTUSAN MEMBELI KORAN JUALBELI - Wihartika, Doni (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2016)
ABSTRACTFormulation of the problemas follows: (1) Has product quality related with buying decision on Koran JualBeli? (2)Has price related with buying decision on Koran JualBeli? (3) Has distribution related with buying decision on Koran JualBeli? (4) Has promotion strategy related with buying decision on Koran JualBeli? (5) Are there relationships between product quality, price, distribution and promotion strategy ofÂ  Koran JualBeliwith buying decision of Koran JualBeli? The place of research is in DTX which is located in Bogor, West Java. The result shows that the product (X1) and the promotion strategy (X4) are not partially correlated with the buying decision (Y), while the price (X2) and the distribution (X3) are partially correlated with the buying decision (Y). Â Keywords: Koran JualBeli, Buying Decision, Distribution, Promotion Strategy